Patient safety: the experience of an Italian teaching hospital (Italian Journal of Public Health, 2005)
Introduction The risk management project of The University Hospital “A. Gemelli” aims to define the necessary procedures to manage clinical risk, by identifying the structures involved within this process, so that all of the personnel can contribute to a measurable improvement in the safety of both patients and staff.Methods The Risk Management Program is comprised of 5 long-term phases: Phase 1 - Strategy Definition and Communication: a clear and shared Risk Management Strategy is indispensable to guarantee a coordinated action plan, in order to focus all of the interventions towards the achievement of common and measurable results. Phase 2 - Risk Management System Governance: all of the organisational structures have been activated in order to effectively manage the Risk Management System. The system has been introduced to interact within all areas of the hospital and to transfer information. Phase 3 - Promotion within the Organisation: this phase fosters the aims of the project within the whole organisation, by stressing the concept of “learning from errors”. This is crucial if organisational and healthcare workers are to understand the true aims of risk prevention and protection and offer to contribute to the process. Phase 4 - Risk Assessment: a data survey system was created and institutionalized. This phase begins with an analysis of the information flow, in order to estimate the probabilities that certain risks occur, and ends with defining the interventions to undertake. Risk assessment makes it possible to forecast the consequences of certain risks and thus prioritise those for prevention. Phase 5 - Risk Management: this consists of planning and implementing all of the actions necessary to prevent risks, protect and finance (in terms of prevention) A. Gemelli University Hospital.Results The results achieved are remarkable especially when one considers the organisation of a complex clinical risk management system within a large university hospital. An information flow that examines and identifies risks from surveying the data has been created. Preventative activities have been planned in the laboratories, transfusion and pharmacotherapy sectors as outlined in the risk map, together with clinical audit activities. Furthermore, all of these issues have been highlighted across all sectors with the creation of an accredited ECM training program as well as the implementation of an anonymous survey. These initiatives have not only increased the interest in Risk Management issues, but have also fostered the integration of different groups and their working methods.Conclusions Introducing risk management processes to A. Gemelli University Hospital represents a step from the promotion and dissemination phase to that of a formal organic risk management system in medicine. This initiative, involving the participation of all personnel, has produced a measurable improvement in safety of both patients and staff.
Keywords: Risk management; clinical risk; survey system; safety